Kespesifikan Biokatalis Dedak Padi dalam Reaksi Pembentukan Antibakteri Monoasilgliserol dari Minyak Kelapa - mappiratu mappiratu (Biocelebes, 2009)
In an effort to analyse the spesification of rice bran lypase and antibacterium activity of monoacylglyserol (MAG) produced from various reaction time, it has been performed glyserolysis of coconut oil for 192 h with observation interval 24 h. It was recorded that lypase of rice bran of variety Maros had a higher spesification for formation of short and intermediate chain monoacylglyserols (MAGs) than sature and unsature long chain MAGs. MAG inhibition on Bacillus cereus and Staphillococcus aureus reached optimum at 72 h reaction time, whilst Vibrio cholerae reached optimum at 192 h and it was insignificantly different with 48, 144 and 168 h. MAG inhibition on the three bacteria strains reached minimum at 92 h. During the reaction period, antimicrobial MAG reached minimum. Key words: Spesification, biocatalyses, rice bran, antibacterium MAG, coconut oil.